(3Pjd GdOQQ GdcGefIs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMGW Hcd TF YdekG hCMUi cd TF YOOkG s
(3BNQgG (B:s
(3hUd ajg Edi SfI (B832(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B137 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs